2019
DOI: 10.1111/imm.13022
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐1β influences functional regeneration following nerve injury in mice through nuclear factor‐κB signaling pathway

Abstract: This study focuses on investigating the role of interleukin-1b (IL-1b) in functional regeneration following nerve injury in mice. A microarraybased mRNA profiling study was used to analyze the expression level of IL-1b in peripheral nerve regeneration. Quantitative real-time polymerase chain reaction and Western blot were applied to assess the IL-1b expressions of C57BL/6J-crush and C57BL/6J-crush+IL-1b mice at different post-injury time-points after the standard sciatic nerve crush injury. The outcomes of ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…IL-1β is an inflammatory factor that is involved in the NF-κB cell signaling pathway. IL-1β binds its receptor, IL-1 receptor, and exerts its effects on the NF-κB kinase NIK, which activates the Iκβ kinase complex and activates NF-κB (45,46). IL-1β may be induced by NF-κB activation, while IL-1β activates an autocrine signal loop that upregulates the NF-κB signal (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…IL-1β is an inflammatory factor that is involved in the NF-κB cell signaling pathway. IL-1β binds its receptor, IL-1 receptor, and exerts its effects on the NF-κB kinase NIK, which activates the Iκβ kinase complex and activates NF-κB (45,46). IL-1β may be induced by NF-κB activation, while IL-1β activates an autocrine signal loop that upregulates the NF-κB signal (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory cytokines secreted by tumor cells are closely related to the progression, invasion, metastasis, and chemotherapeutic resistance of malignant tumors. High concentration of IL‐1 in tumor microenvironment is closely related to malignant phenotype of tumor, and tumor patients with high expression of IL‐1 have poor clinical prognosis (Wu et al ). IL‐1 can also enhance the invasiveness of existing tumors, mainly by initiating new angiogenesis, leading to tumor proliferation and metastasis (Voronov et al ).…”
Section: Discussionmentioning
confidence: 99%
“…The basic function of IL-1α is to induce the generation of IL-6 and granulocyte–macrophage colony-stimulating factor (GM-CSF) in fibroblasts in situ, which can be detected within 2 to 5 h after an injury [ 26 ]. IL-1β may promote nerve regeneration via the nuclear factor-κB (NF-κB) signaling pathway [ 27 ]. Previous studies suggested that there are low levels of IL-1β one hour after injury, but one-day post-injury—before macrophage recruitment—the secretion of IL-1β peaks [ 28 ], 6 and 24 h after injury, the expression levels of IL-1β is 2 times and 10 times higher than in the control groups [ 29 , 30 ].…”
Section: Mscs Exert Immunomodulatory Effects By Modulating Cytokine Expressionmentioning
confidence: 99%
“…Previous studies suggested that there are low levels of IL-1β one hour after injury, but one-day post-injury—before macrophage recruitment—the secretion of IL-1β peaks [ 28 ], 6 and 24 h after injury, the expression levels of IL-1β is 2 times and 10 times higher than in the control groups [ 29 , 30 ]. High levels of IL-1β are maintained for several days [ 27 ], gradually decreasing and finally returning to the baseline levels around 14 days after PNI. MSCs can reduce IL-1 expression: for instance, a study by Chen et al reported that bone-marrow-derived MSCs significantly reduced the expression of IL-1β in mice following spinal cord injury (SCI) [ 31 ].…”
Section: Mscs Exert Immunomodulatory Effects By Modulating Cytokine Expressionmentioning
confidence: 99%